Cross-sectional study of patients with Trigeminal Neuralgia treated at the Walter Cantídio Hospital of the Federal University of Ceará (Research, Society and Development, 2022)
Trigeminal Neuralgia is described as excruciating pain, similar to an electric shock that affects one or more branches of the trigeminal nerve. The treatment of Trigeminal Neuralgia (TN) remains a therapeutic challenge. Pharmacological treatment is the first choice, however many patients become intolerant to it, being referred to surgery. Thus, this study aimed to evaluate data from a group of patients diagnosed with trigeminal neuralgia (TN) treated at the Walter Cantídio University Hospital of the Federal University of Ceará, focusing on sociodemographic data, symptoms and treatment type. The following data were collected on age, sex, anamnesis, reported symptoms, diagnosis, comorbidities, treatment and evolution. Data from 62 patients obtained from medical records during the follow-up period were included. The results showed that the incidence in all age groups was primarily in females, the most reported symptom was unilateral shock pain. 25% of patients associated the onset of symptoms with a previous event such as tooth extraction, endodontic treatment or trauma. The drug of choice for treatment was carbamazepine in 74% of patients, 20% of patients did not control pain with treatment and underwent surgery. Therefore, more advances in scientific studies regarding pain mechanisms and the discovery of more precise drugs to control it will be the way to treat trigeminal neuropathic pain.